Multimodal Analysis of Interactive Meaning in Selected Picture Book Biographies About Greta Thunberg (TRANSFORM: Journal of English Language Teaching and Learning, 2023)
This study aimed at identifying the types of interactive meanings, the use of interactive meaning in illustration and phrases of two picture book biographies about Greta Thunberg and the compatibility between the interactive meaning in illustrations and phrases of two picture book biographies about Greta Thunberg, Greta and The Giants and Little People Big Dreams “ Greta Thunberg. This study was conducted by applying descriptive qualitative method. The sources of data were taken from two picture books. The research instrument was the researcher herself by using a tool including laptop and books. The results of this research showed that in Greta and The Giants, there were thirteen types of interactive meaning with the total of 22 illustrations. As for the results in Little People Big Dreams “ Greta Thunberg, there were ten out of thirteen types of interactive meaning with the total of 13 illustrations. The total number of data were 35 illustrations and 130 phrases. Interactive meaning in Greta and The Giants and Little People Big Dreams “ Greta Thunberg were both compatible to giving information about climate change awareness.
Keywords: Picture Books; Multimodal Analysis